The Invisible Struggles: A Qualitative Study in Understanding Mothers’ Perceptions and Experiences in Nurturing Small for Gestational Age Infants - Ahmad, Norain; Sutan, Rosnah; Mohd Tamil, Azmi; Hajib, Noriah (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Small for gestational age (SGA) infants have been linked to poor growth trends and nutritional status. SGA infants that do not reach their full growth potential must be supervised by a multidisciplinary medical team. Parents devote more time, energy, and money for raising of the SGA infants. The objective of this present study is to explore the perceptions and the experiences of the mother in nurturing the small for gestational age infants in their first year of life. Method: A qualitative exploratory descriptive study via in-depth interview was conducted in the primary health clinics in urban areas in Malaysia to explore the mothers’ perceptions and experiences in SGA infant’s care. 13 SGA infant’s mothers participated in the study after the children achieved the age of one year old. Thematic analysis was conducted using software ATLAS.ti version 8. Results: The average mothers’ age in this study were 33 years old, majority was Malay ethnicity. Only one mother was a housewife and others were working mother. Four out of 13 SGA infants were born prematurely. This study found that homogenous experiences throughout the pregnancy and baby nurturing phase, perceptions on husband involvement and external supports in infant care, infant health status and health services provided, were highlighted as important contributor to infant survival. Conclusion: The importance of monitoring SGA infant growth and nutritional status have been highlighted. Maternal psychological support needs to be enhanced to ease the burden in SGA infant care. Targeted program intervention for family and community social support during postnatal and empowering mothers in nurturing their infants are crucial.